2014
DOI: 10.1590/0102-311x00163812
|View full text |Cite
|
Sign up to set email alerts
|

Age, class and race discrimination: their interactions and associations with mental health among Brazilian university students

Abstract: Although research on discrimination and health has progressed significantly, it has tended to focus on racial discrimination and US populations. This study explored different types of discrimination, their interactions and associations with common mental disorders among Brazilian university students, in Rio de Janeiro in 2010. Associations between discrimination and common mental disorders were examined using multiple logistic regression models, adjusted for confounders. Interactions between discrimination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 34 publications
4
57
0
16
Order By: Relevance
“…30 The number of reasons for being discriminated against was not associated with patterns of alcohol consumption in the whole UFSC sample, but over half of the students reported more than one reason for being discriminated against. In our review of the literature, the only two studies that examined the association between multiple reasons for being discriminated against and adverse health conditions found positive results, 8,21 which support the hypothesis that discriminatory experiences attributed to multiple reasons may have worse health effects.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…30 The number of reasons for being discriminated against was not associated with patterns of alcohol consumption in the whole UFSC sample, but over half of the students reported more than one reason for being discriminated against. In our review of the literature, the only two studies that examined the association between multiple reasons for being discriminated against and adverse health conditions found positive results, 8,21 which support the hypothesis that discriminatory experiences attributed to multiple reasons may have worse health effects.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, recent studies suggest the existence of a possible association between discrimination and alcohol use or abuse. 4,[6][7][8][9][10] Alcohol use or abuse is a considerable problem in contemporary societies, and it is closely associated with negative short-and long-term health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A nationally-representative sample showed that self-identified Black Brazilians reported higher levels of racial discrimination (37%) than Browns (10%) or Whites (6.7%), with similar race gaps whether interviewer-classified race or respondent self-classification was used 7 . Finally, Black and Brown university students in Rio de Janeiro reported more discrimination that they attributed to their race -or a combination of multiple identities, including race -than did their White counterparts, while Whites reported more discrimination on the basis of class, age, and for other reasons 6 .…”
Section: Introductionmentioning
confidence: 90%
“…Most of the extant research on perceived discrimination has been conducted in the United States, a society with a long history of institutionalized racial discrimination, but one that experienced a Civil Rights movement in the 1960s that led to legal restrictions on racial discrimination, and a need to monitor compliance with these new laws. Researchers in other societies have also begun to explore the prevalence of perceived racial discrimination in the context of their own distinctive social and legal histories around race, such as South Africa 3 and Brazil 4,5,6,7 . Brazil stands out as a society without racially-discriminatory laws after the abolition of slavery, and a unique reputation as a supposed "racial democracy" as compared to other multiracial societies, but only recently has begun to officially acknowledge the persistence of racebased inequalities and discrimination.…”
Section: Introductionmentioning
confidence: 99%